2021
DOI: 10.1007/s15010-021-01659-w
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory parameters and outcomes in hospitalized adults with COVID-19: a scoping review

Abstract: Background Laboratory parameters and the associated clinical outcomes have been an area of focus in COVID-19 research globally. Purpose We performed a scoping review to synthesize laboratory values described in the literature and their associations with mortality and disease severity. Methods We identified all primary studies involving laboratory values with clinical outcomes as a primary endpoint by performing data searches in various systematic review databases until 10th August, 2020. Two reviewers independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…However, similar results were found in China (Chen et al, 2020;Chen et al, 2021). High levels of urea predict mortality in UK and other countries (Aloisio et al, 2020;Zhu et al, 2022;Burke et al, 2022). Liver enzymes increase gradually with COVID-19 severity (Guan et al, 2020;Chen et al, 2021) and are high in approximately 25% of patients (Wijarnpreecha et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, similar results were found in China (Chen et al, 2020;Chen et al, 2021). High levels of urea predict mortality in UK and other countries (Aloisio et al, 2020;Zhu et al, 2022;Burke et al, 2022). Liver enzymes increase gradually with COVID-19 severity (Guan et al, 2020;Chen et al, 2021) and are high in approximately 25% of patients (Wijarnpreecha et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…In Africa, few data on biological characteristics of COVID-19 patients are available. In their meta-analysis of 13,568 articles, Zhu Andrew et al (Zhu et al, 2022) found that most data came from Asia, followed by Europe, then North and South America. No data from Africa were mentioned in that study.…”
mentioning
confidence: 99%
“…Aunque las pruebas de laboratorio de rutina son poco específicas para la infección por SARS-CoV-2, pueden orientar hacia la determinación de la severidad de la enfermedad y su pronóstico, además de facilitar el seguimiento del paciente [42,43]. Las alteraciones encontradas en pacientes infectados son principalmente cambios en el hemograma (linfopenia), aumento de los valores de las enzimas hepáticas, la creatinina y la urea, y de los marcadores inespecíficos de inflamación y lesión, como la proteína C reactiva (PCR), la enzima lactato deshidrogenasa (LDH), el dímero D y la ferritina [43].…”
Section: Pruebas Complementarias En El Diagnóstico De Covid-19unclassified
“…Moreover, it is quite surprising that in the present study a limited number of comorbidities were reported in the study population considering that COVID-19 patients usually present a high rate of comorbidities which in turn have a remarkable impact on clinical outcomes [ 3 ]. Finally, there was no relationship between CT severity score and crucial laboratory parameters recurrently used during COVID-19 pandemic such as transferrin, lactate dehydrogenase, troponin, and inflammation related factors of leucocytes, neutrophils, and IL-2R [ 10 ].…”
mentioning
confidence: 99%